Gambaran Budaya Keselamatan Pasien di Rumah Sakit: Tinjauan Pustaka - Amallia, Rizka Dina; Pramesona, Bayu Anggileo; Setiawan, Gigih; Saftarina, Fitria (CV. Jasa Sukses Abadi, 2025)
Patient safety culture is the key to providing high-quality and safe healthcare services. All healthcare providers, especially nurses, must be committed to creating and maintaining a strong patient safety culture. This research aims to gain a deep understanding of patient safety culture. The method used is a literature study taken from PubMed and Google Scholar databases published within the last 5 years and relevant to the topic. The selected articles are those that are fully available, focus on hospitals as the research site, and are written in Indonesian or English. The research shows that a good patient safety culture, characterized by leadership support, teamwork, open communication, and an effective incident reporting system, can improve the quality of healthcare and reduce risk of medical errors. However, many hospitals have not fully implemented a patient safety culture optimally. Some common challenges include low incident reporting rates, lack of leadership support, and a lack of a learning culture from mistakes. To address this problem, continuous efforts are needed to build a strong patient safety culture, such as increasing staff awareness, providing training, and creating safe environment for reporting errors.